Main trends in providing medical personnel to the state healthcare system of the Russian Federation - Z. Kh. Agamov; E. V. Aziattseva; D. A. Doronshoeva; R. T. Savzikhanov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2024)
The purpose of this study is to analyze trends in the provision of medical personnel to the state health care system during the implementation of state programs and national projects in the field of health care. Materials and methods. Statistical collections of the Ministry of Health of Russia for 2012–2023, regulatory legal acts, passport of national project. Methods of descriptive statistics and analytical were used. Results. A reduction in indicators of the supply of doctors, paramedical personnel and the ratio of doctor/nursing medical personnel and a discrepancy between their target values established in state programs and national projects for the development of healthcare was revealed. Differences in the values of target indicators of state programs and national projects have been identified. Conclusion. The need to take urgent measures to eliminate the reduction in the supply of medical personnel has been identified. Differences in the dynamics of staffing indicators indicate the heterogeneity of the level of development of regions and their preparedness for events within the framework of state programs and national projects to achieve target indicators. Measures are needed to eliminate territorial imbalances, as well as to search for mechanisms to equalize differences between the constituent entities of the Russian Federation. Differences in the values of indicators for achieving the goals of state programs and national projects complicate their assessment and determine the need to form a hierarchy of state programs and national projects, as well as the development of scientifically based target indicators, taking into account regional characteristics and the needs of the population for medical care.